Geomorfología y peligros de la subcuenca del río Auqui (Calcayhuanca), Huaraz, Áncash - Melendez de la Cruz, Juan Felipe (2008)
The peripheric and urban expansion area of Huaraz is taking place on the lower part of Anqui River’s Sub Basin, between 3,200 and 3,500 m.a.s.l. These areas were traditionally used to develop agricultural and livestock activities. Nevertheless, because of the economic boom of Huaraz, these areas are being urbanized slowly but constantly. The lower part of the basin is a natural area of fluvioglaciar sedimentation and mass motion (water, mud, and rock avalanches). In the highest parts of the basin the origin of the above mentioned natural process is the glaciar erosion and fusion of the glaciar mass. The incidence of avalanches, which could affect the lower part of the basin is slow. Nevertheless, the chance of having one like in 1941 or 1970 is not to be ruled out because Perú is a highly seismic country.